2017
DOI: 10.1007/s12035-017-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased Root Canal Endotoxin Levels are Associated with Chronic Apical Periodontitis, Increased Oxidative and Nitrosative Stress, Major Depression, Severity of Depression, and a Lowered Quality of Life

Abstract: Evidence indicates that major depression is accompanied by increased translocation of gut commensal Gram-negative bacteria (leaky gut) and consequent activation of oxidative and nitrosative (O&NS) pathways. This present study examined the associations among chronic apical periodontitis (CAP), root canal endotoxin levels (lipopolysaccharides, LPS), O&NS pathways, depressive symptoms, and quality of life. Measurements included advanced oxidation protein products (AOPP), nitric oxide metabolites (NOx), lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 81 publications
(107 reference statements)
2
68
0
3
Order By: Relevance
“…The first major finding of this study is that MDA, AOPP, the nitro‐oxidative stress index, and lowered CMPAase activity are associated with the different HRQoL domains, especially with physical and social relationships. We are not aware of any studies showing a relationship between MDA and HRQoL in mood disorders, while a prior study found AOPP to be inversely associated with HRQoL in patients with depression due to periodontitis . In women with postmenopausal osteoporosis, HRQoL subdomains, including pain and mental and social functions, correlate with NO levels and antioxidant enzyme activities, but not MDA .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The first major finding of this study is that MDA, AOPP, the nitro‐oxidative stress index, and lowered CMPAase activity are associated with the different HRQoL domains, especially with physical and social relationships. We are not aware of any studies showing a relationship between MDA and HRQoL in mood disorders, while a prior study found AOPP to be inversely associated with HRQoL in patients with depression due to periodontitis . In women with postmenopausal osteoporosis, HRQoL subdomains, including pain and mental and social functions, correlate with NO levels and antioxidant enzyme activities, but not MDA .…”
Section: Discussionmentioning
confidence: 71%
“…In women with postmenopausal osteoporosis, HRQoL subdomains, including pain and mental and social functions, correlate with NO levels and antioxidant enzyme activities, but not MDA . Increased MDA levels are detected in MDD, BD, patients with prior suicidal attempts, severe depression, TUD, and metabolic syndrome, while increased levels of AOPP are detected in suicide, major depression, and prenatal depression . Increased MDA and AOPP levels are oxidative damage biomarkers, which may cause (neuro)degenerative processes including arteriosclerosis and neurodegeneration, which both may be linked to lowered HRQoL scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that increased root canal endotoxin levels were associated with increased oxidative stress, severity of depression, and a lowered quality of life (Gomes et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…It should be underscored that MDD and BP disorder are characterized by reduced -SH groups and glutathione levels in serum or brain. [33][34] By inference, MDD and BP1, but not BP2, appear to be associated with increased production of NO metabolites which may induce increased nitrosylation, which in turn may damage both the glutathione system and SH-groups thereby attenuating key components of the antioxidant defense. These findings further extent our recent report that the (partially) remitted phase of MDD and BP1, but not BP2, is accompanied by increased signs of nitro-oxidative stress and breakdown of antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%